Reflective mask blanks and reflective masks
Patent Information
- Application Number
- JP2020085399
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-14
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-05-14
AI Technical Summary
【0011】 本発明の一態様に係る反射型マスク、及びそれを作製するための反射型マスクブランクによれば、EUV光吸収率が高く、ドライエッチング可能な吸収膜を使用するため、従来よりも薄いレジスト膜厚が使えるようになり、微細な高吸収膜パターンを形成することが可能となる。その結果、射影効果を軽減することができ、ウェハ上で線幅誤差やパターンの位置ずれを低減することが可能となる。また、電子線修正エッチングが可能となる。 このように、本発明の一態様に係る反射型マスク、及びそれを作製するための反射型マスクブランクであれば、EUVマスクの吸収膜として高吸収性材料を使用した場合であっても、微細な吸収膜パターンが形成されており、従って射影効果を軽減することができ、且つ電子線修正エッチングを可能とする反射型マスク、及びそれを作製するための反射型マスクブランクを提供することができる。
Smart Images

Figure 0007640231000003 
Figure 0007640231000004 
Figure 0007640231000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a reflective mask blank and a reflective mask. [Background technology]
[0002] In the manufacturing process of semiconductor devices, the demand for miniaturization of photolithography technology is increasing along with the miniaturization of semiconductor devices. In photolithography, the minimum resolution dimension of the transfer pattern is highly dependent on the wavelength of the exposure light source, and the shorter the wavelength, the smaller the minimum resolution dimension can be. For this reason, in the manufacturing process of semiconductor devices, the conventional exposure light source using ArF excimer laser light with a wavelength of 193 nm is being replaced by an EUV (Extreme UltraViolet) exposure light source with a wavelength of 13.5 nm.
[0003] Since EUV light has a short wavelength, most substances have high light absorption. Therefore, photomasks for EUV (EUV masks) are reflective masks, unlike conventional transmission masks (see, for example, Patent Document 1 and Patent Document 2). Patent Document 1 discloses that in a reflective exposure mask used in EUV lithography, a multilayer film is formed by periodically stacking two or more types of material layers on a base substrate, and a mask pattern is formed on the multilayer film, which is made of a metal film containing a nitride, or a mask pattern made of a laminated structure of a metal nitride film and a metal film. Patent Document 2 discloses a reflective EUV mask in which a pattern made of a metal film containing an ion-implanted element is formed as an absorbing film on a multilayer reflective film.
[0004] In addition, as mentioned above, EUV lithography cannot use refractive optics that utilize the transmission of light, so the optical components of the exposure machine are mirrors rather than lenses. This creates a problem in that the incident light and reflected light on the EUV photomask cannot be designed to be coaxial, so EUV lithography normally employs a method in which the EUV light is incident with the optical axis tilted 6 degrees from the vertical direction of the EUV photomask, and the reflected light reflected at an angle of minus 6 degrees is irradiated onto the semiconductor substrate. As such, because EUV lithography tilts the optical axis, the EUV light entering the EUV photomask can cast a shadow on the EUV photomask pattern (absorbing film pattern), which can degrade the transfer performance and cause a problem known as the "projection effect."
[0005] To address this problem, Patent Document 2 discloses a method in which a material with a high extinction coefficient k is ion-implanted into the absorbing film to increase the absorption coefficient k for EUV light and suppress the EUV reflectance, thereby enabling the absorber layer to have a thinner thickness (60 nm or less) than before and reducing the projection effect. As miniaturization advances, dry etching has become common for patterning light-shielding films in transmission photomasks, and dry etching is also used for patterning absorbing films in EUV masks. However, in general, the material with a high extinction coefficient k for EUV used in Patent Document 2 is a material with a low dry etching rate. Therefore, the processability of the absorbing film is poor, and the resist that serves as the etching mask must also be thick, resulting in a problem that it is difficult to form a fine absorbing film pattern using a highly absorbing material.
[0006] Furthermore, when performing electron beam repair etching in the defect repair process of the photomask manufacturing process, materials with a high extinction coefficient k have an extremely slow etching rate, which can be a major problem as they are difficult to repair defects with. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2004-6798 A [Patent Document 2] JP 2015-73013 A Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made to solve the above problems, and an object of the present invention is to provide a reflective mask in which a fine absorbing film pattern is formed even when a highly absorbing material is used as the absorbing film of an EUV mask, thereby reducing the projection effect and enabling electron beam correction etching, and a reflective mask blank for producing the same. [Means for solving the problem]
[0009] In order to achieve the above object, a reflective mask blank according to one embodiment of the present invention is a reflective mask blank having a substrate, a reflective film having a multilayer structure formed on the substrate and reflecting EUV light, a protective film formed on the reflective film and protecting the reflective film, and an absorbing film formed on the protective film and absorbing EUV light, wherein the absorbing film contains 50 atomic % or more of an element constituting at least one of tin oxide and indium oxide, and contains a material that is easily etched by a fluorine-based gas or a chlorine-based gas.
[0010] Moreover, a reflective mask according to one embodiment of the present invention is a reflective mask comprising a substrate, a reflective film having a multilayer structure formed on the substrate and reflecting EUV light, a protective film formed on the reflective film and protecting the reflective film, and an absorbing film formed on the protective film and absorbing EUV light, wherein the absorbing film contains 50 atomic % or more of elements constituting at least one of tin oxide and indium oxide, and contains a material that is easily etched by a fluorine-based gas or a chlorine-based gas. Effect of the Invention
[0011] According to a reflective mask according to one embodiment of the present invention, and a reflective mask blank for fabricating the same, an absorbing film that has a high EUV light absorptance and can be dry-etched is used, so that a thinner resist film thickness than before can be used, and a fine highly absorbing film pattern can be formed. As a result, the projection effect can be reduced, and line width errors and pattern position deviations on the wafer can be reduced. In addition, electron beam correction etching is possible. In this way, with a reflective mask according to one embodiment of the present invention, and a reflective mask blank for producing the same, even when a highly absorbing material is used as the absorbing film of an EUV mask, a fine absorbing film pattern is formed, thereby making it possible to provide a reflective mask that can reduce the projection effect and enables electron beam correction etching, and a reflective mask blank for producing the same. [Brief description of the drawings]
[0012] [Figure 1] 1 is a schematic cross-sectional view showing a structure of a reflective photomask blank according to an embodiment of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing a structure of a reflective photomask according to an embodiment of the present invention. [Diagram 3] 1 is a graph showing the optical constants of each metal at the wavelength of EUV light. [Figure 4] 1 is a graph showing a simulation result of the reflectance of a reflective photomask blank according to an embodiment of the present invention for EUV light. [Diagram 5] 1 is a graph showing a simulation result of an OD value at the wavelength of EUV light of a reflective photomask blank according to an embodiment of the present invention. [Figure 6] FIG. 1 is a schematic cross-sectional view showing side etching after electron beam correction etching of a single-layer absorber film made of tin oxide. [Figure 7] FIG. 1 is a schematic cross-sectional view showing a structure of a reflective photomask blank according to an embodiment of the present invention. [Figure 8] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 9] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 10] 1A to 1C are schematic cross-sectional views showing a manufacturing process of a reflective photomask according to an embodiment of the present invention. [Figure 11] 5A to 5C are schematic cross-sectional views showing a repair process of a reflective photomask according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, each configuration of the reflective photomask blank and the reflective photomask according to the present invention will be described with reference to the drawings. (Overall structure) Fig. 1 is a schematic cross-sectional view showing the structure of a reflective photomask blank (reflective mask blank) 10 according to an embodiment of the present invention. Fig. 2 is a schematic cross-sectional view showing the structure of a reflective photomask (reflective mask) 20 according to an embodiment of the present invention. Here, the reflective photomask 20 according to the embodiment of the present invention shown in Fig. 2 is formed by patterning the absorbing film 4 of the reflective photomask blank 10 according to the embodiment of the present invention shown in Fig. 1. 1, a reflective photomask blank 10 according to an embodiment of the present invention includes a multilayer reflective film (reflective film) 2 on a substrate 1, and a capping layer (protective layer) 3 on the multilayer reflective film 2. Thus, the multilayer reflective film 2 and the capping layer 3 are formed on the substrate 1. An absorbing film 4 is provided on the capping layer 3, and the absorbing film 4 is composed of at least one layer.
[0014] (substrate) The substrate 1 according to the embodiment of the present invention may be a flat Si substrate, a synthetic quartz substrate, etc. The substrate 1 may be made of low thermal expansion glass containing titanium, but the present invention is not limited to these materials as long as they have a small thermal expansion coefficient. (Multilayer reflective film) The multilayer reflective film 2 according to the embodiment of the present invention reflects EUV light (extreme ultraviolet light) which is exposure light, and is composed of a multilayer reflective film made of a combination of materials with significantly different refractive indices for EUV light. For example, the multilayer reflective film 2 can be formed by repeatedly stacking layers of a combination of Mo (molybdenum) and Si (silicon), or Mo (molybdenum) and Be (beryllium), for example, for about 40 periods.
[0015] (capping layer) The capping layer 3 according to the embodiment of the present invention is formed of a material that is resistant to the dry etching performed when forming the pattern of the absorbing film 4, and functions as an etching stopper that prevents damage to the multilayer reflective film 2 when etching the absorbing film pattern. Here, the capping layer 3 may not be necessary depending on the material of the multilayer reflective film 2 and the etching conditions. Although not shown, a back conductive film can be formed on the surface of the substrate 1 on which the multilayer reflective film 2 is not formed. The back conductive film is a film for fixing the reflective photomask 20 by utilizing the principle of an electrostatic chuck when the reflective photomask 20 is placed in an exposure machine.
[0016] As shown in FIG. 2, an absorbing pattern (absorbing film pattern 14a) of a reflective photomask 20 is formed by removing a part of the absorbing film 4 of the reflective photomask blank 10, i.e., by patterning the absorbing film 4. In EUV lithography, EUV light is incident at an angle and reflected by the reflective film 12, but due to a projection effect in which the absorbing film pattern 14a obstructs the optical path, the transfer performance onto a wafer (semiconductor substrate) may deteriorate. This deterioration in transfer performance can be reduced by reducing the thickness of the absorbing film pattern 14a that absorbs EUV light. In order to reduce the thickness of the absorbing film pattern 14a, it is preferable to use a material that is more absorbent for EUV light than conventional materials, that is, a material with a high extinction coefficient k at a wavelength of 13.5 nm.
[0017] Figure 3 is a graph showing the optical constants of each metal material for EUV light with a wavelength of 13.5 nm. The horizontal axis of Figure 3 represents the refractive index n, and the vertical axis represents the extinction coefficient k. The extinction coefficient k of tantalum (Ta), which is the main material of the conventional absorbing film 4, is 0.041. If a compound material has a larger extinction coefficient k than this, it is possible to make the thickness of the absorbing film 4 thinner than before. If a material with an extinction coefficient k of 0.06 or more is used as the main component, it is possible to make the thickness of the absorbing film 4 sufficiently thin, and the projection effect can be reduced.
[0018] As shown in FIG. 3, materials that satisfy the above combination of optical constants (nk value) include, for example, silver (Ag), indium (In), tin (Sn), nickel (Ni), and tellurium (Te), and their extinction coefficients k are in the range of 0.07 to 0.08. The extinction coefficient k of the above materials can be significantly increased to about twice the extinction coefficient k of tantalum (Ta), which is a conventional absorbing film material, that is, 0.041, and therefore high light absorption can be obtained. However, most of these highly absorbing materials are difficult to process into masks due to poor dry etching properties (in other words, the volatility of the halides of these elements is low), or they cannot withstand the heat during mask fabrication or EUV exposure due to their low melting points, and therefore are poorly practical for use as masks.
[0019] In order to avoid such defects, the absorbing film 4 of the reflective photomask blank 10 and the absorbing film pattern 14a of the reflective photomask 20 according to this embodiment are formed of a tin oxide (SnO) film or an indium oxide (InO) film. The melting points of tin (Sn) alone and indium (In) alone are low, around 230°C and 160°C, respectively, and have problems with thermal stability, but by using a tin oxide (SnO) film or an indium oxide (InO) film, the melting points of each can be significantly increased. In fact, multiple tin oxide (SnO) films were produced by reactive sputtering, and their melting points were measured using a thermal analyzer. As a result, it was found that the tin oxide (SnO) film had a melting point of 1630°C and the indium oxide (InO) film had a melting point of 1910°C, which is higher than that of each of the individual elements.
[0020] Furthermore, since tin oxide (SnO) films and indium oxide (InO) films are chemically stable, they tend not to be easily etched by fluorine-based gases (e.g., fluorine-containing etching gases such as CF4 gas and SF6 gas) or chlorine-based gases (e.g., chlorine-containing etching gases such as Cl2 gas and HCl gas) that are commonly used in dry etching. In this case, since the dry etching rate is low, the resist formed on the absorbing film 4 also needs to be thick, and as a result, it tends to be difficult to form a fine absorbing film pattern 14a.
[0021] In response to this, by mixing a material that is easily etched by a fluorine-based gas or a chlorine-based gas into a tin oxide (SnO) film or an indium oxide (InO) film, respectively, the etching rate when using a fluorine-based gas or a chlorine-based gas can be improved. This allows the resist film thickness on the absorbing film 4 to be thin, and as a result, the difficulty of forming a fine absorbing film pattern 14a using a highly absorbing material can be reduced. In general, in dry etching, the introduced gas collides with electrons in the plasma, generating active radicals and reactive ions dissociated into various forms, which causes etching. The more volatile products with low boiling points are formed on the etching surface, the more easily the material is etched. The boiling point and vapor pressure of the reaction products between the material to be etched and the introduced gas are used as indicators. In other words, the lower the boiling point of the reaction product, the more it vaporizes, the higher the vapor pressure, and the easier it is to exhaust.
[0022] In the etching of the absorbing film 4 of the reflective photomask blank 10, the definitions of the above-mentioned terms "easily etched" and "hardly etched" will be explained below. The case where a material is easily etched by a chlorine-based gas means that at least one chlorine-based compound produced by etching has a boiling point of 250° C. or lower, and the case where a material is not easily etched by a chlorine-based gas means that the boiling point of a stoichiometric chloride produced by etching is 300° C. or higher. The same applies to fluorine-based gases.
[0023] The absorbing film 4 of the reflective photomask blank 10 and the absorbing film pattern 14a of the reflective photomask 20 according to the embodiment of the present invention are tin oxide (SnO) films or indium oxide (InO) films containing a mixed material that is easily etched by fluorine-based gas or chlorine-based gas, and the atomic ratio of the mixed material to tin oxide (SnO) or indium oxide (InO) is in the range of more than 0% and not more than 45%. That is, the atomic ratio of tin oxide (SnO) or indium oxide (InO) is more than 50% and less than 100%. If the compound material is in this range, the refractive index, which is an optical constant for EUV light, hardly changes. In addition, although the extinction coefficient k changes depending on the atomic ratio, the absorbing film 4 (absorbing film pattern 14a) can achieve a film thickness of 45 nm or less and an EUV reflectance of 3% or less. As a result, a tin oxide (SnO) film or an indium oxide (InO) film, which contains a mixed material that is easily etched by fluorine-based or chlorine-based gases, can have higher light absorption properties than tantalum (Ta), which is the material used to form existing absorbing films.
[0024] In fact, when several tin oxide (SnO) film samples containing silicon (Si) were produced with varying amounts of each metal, with the tin oxide (SnO) content ranging from more than 50% to less than 100%, and the reflectance at the EUV light wavelength (13.5 nm) was measured, it was found that an EUV reflectance of 3% or less could be achieved with a film thickness thinner than that of existing tantalum (Ta) absorption films (approximately 60 nm). In other words, the reflective mask blank 10 according to this embodiment comprises a substrate 1, a reflective film 2 having a multilayer structure formed on the substrate 1 and reflecting EUV light, a capping layer 3 formed on the reflective film 2 to protect the reflective film 2, and an absorbing film 4 formed on the capping layer 3 and absorbing EUV light, wherein the absorbing film 4 contains 50 atomic % or more of elements constituting at least one of tin oxide (SnO) and indium oxide (InO), and contains a material that is easily etched by a fluorine-based gas or a chlorine-based gas.
[0025] Moreover, the reflective mask 20 according to this embodiment has a substrate 11, a reflective film 12 having a multilayer film structure formed on the substrate 11 and reflecting EUV light, a capping layer 13 formed on the reflective film 12 and protecting the reflective film 12, and an absorbing film pattern 14a formed on the capping layer 13 and absorbing EUV light, the absorbing film pattern 14a containing 50 atomic % or more of elements constituting at least one of tin oxide (SnO) and indium oxide (InO) and containing a material that is easily etched by a fluorine-based gas or a chlorine-based gas.
[0026] In order to realize the above etching process, it is preferable to use a material that is easily etched by fluorine-based gas or chlorine-based gas, that is, a substance with a low boiling point of fluorine-based compound or chlorine-based compound, as the material to be mixed with the absorbing film 4 (absorbing film pattern 14a). In other words, it is preferable to select a material that has a lower boiling point in a fluorinated or chlorinated state as the material to be mixed with the absorbing film 4 (absorbing film pattern 14a).
[0027] Table 1 shows the boiling points of tin (Sn) and indium (In), which are suitable as the absorbent (main component) of the reflective photomask 20 according to this embodiment, and halogen-based compounds of metals, which are suitable as the mixed material. The values in Table 1 are a summary of values found in various documents (CRC Handbook of Chemistry and Ohysics, 97th Edition (2016), etc.) and websites. As shown in Table 1, silicon, antimony, iridium, osmium, rhenium, tungsten, germanium, arsenic, vanadium, selenium, molybdenum, and tantalum are preferable as mixed materials that are easily etched by fluorine-based gases. Silicon, chromium, germanium, arsenic, vanadium, titanium, tantalum, aluminum, etc. are preferable as mixed materials that are easily etched by chlorine-based gases. In addition, oxides, nitrides, oxynitrides, or boron nitride compounds of these mixed materials may be used. In addition, a mixed gas of a fluorine-based gas and a chlorine-based gas may be used as the etching gas, and may contain a non-halogen gas such as oxygen gas or hydrogen gas to promote the reaction.
[0028] [Table 1]
[0029] The first optical characteristic required for a photomask to realize transfer by projection exposure, not limited to EUV exposure, is the mask contrast. Normally, in a transmission mask, the mask contrast is evaluated by the following formula (1), where T0 is the transmittance transmitted through the transparent substrate and T is the transmittance transmitted through the pattern portion including the light-shielding film. OD = -log(T / T0) (1) Here, OD is called optical density and indicates the degree of light blocking ability of the light blocking film. The mask contrast can also be evaluated in a similar manner for EUV masks. If the reflectance of the high-reflectivity portion consisting of the multilayer reflective film 12 and the protective film 13 is R0 and the reflectance of the low-reflectivity portion including the absorbing film pattern 14a is R (see FIG. 2), then the mask contrast can be evaluated using the following formula (2), just like for transmission masks. OD = -log(R / R0) (2)
[0030] In the reflective photomask blank 10 and the reflective photomask 20, generally, the higher the OD value, the more preferable. The EUV light reflectance shown in Fig. 4 and the OD value shown in Fig. 5 are calculated using the optical constants (refractive index, extinction coefficient) and film thicknesses of each layer for the reflective photomask blank 10, which has a capping layer (protective layer) 3 made of Ru with a thickness of 2.5 nm under the absorbing film 4, a multilayer reflective film 2 made of a plurality of laminated films (e.g., 40 pairs) each made of a pair of Si and Mo under that, a flat synthetic quartz substrate (substrate 1) under that, and a back conductive film made of chromium nitride (CrN) on the back surface of the synthetic quartz substrate. In other words, the OD value is calculated based on a configuration in which a back conductive film is provided on the back surface of the substrate 1 of each of the reflective photomask blank 10 shown in Fig. 1 and the reflective photomask 20 shown in Fig. 2. However, the materials and film thicknesses of the multilayer reflective films 2, 12, capping layers 3, 13, rear conductive films and substrates 1, 11 of the reflective photomask blank 10 and reflective photomask 20 according to this embodiment are not limited to these.
[0031] As can be seen from Figure 4, a tin oxide (SnO) film containing silicon (Si) can significantly reduce the EUV light reflectance compared to a tantalum (Ta) film, for example, at the same film thickness. Also, a tin oxide (SnO) film containing silicon (Si) can significantly reduce the film thickness compared to a tantalum (Ta) film, at the same reflectance. In this way, a tin oxide (SnO) film containing tantalum (Ta) is effective as a component of a highly absorbing film at the wavelength of EUV light. 5, in order to obtain an OD value of 1 or more, a tantalum (Ta) film needs to be at least 40 nm thick, whereas a tin oxide (SnO) film containing silicon (Si) only needs to be about 18 nm thick. Thus, it can be seen that a tin oxide (SnO) film containing silicon (Si) is effective as a component that can reduce the overall thickness of the absorbing film 4, compared to a tantalum (Ta) film, also from the viewpoint of the OD value.
[0032] Moreover, to obtain an OD value of 2 or more, a tantalum (Ta) film must be at least 70 nm thick, whereas a tin oxide (SnO) film containing silicon (Si) only needs to be 33 nm thick. Thus, it can be seen that a tin oxide (SnO) film containing silicon (Si) is effective as a component that can reduce the overall thickness of the absorbing film 4, even at an OD value of 2 or more, compared to a tantalum (Ta) film. In conventional absorbing films, a tantalum (Ta) film with a thickness of about 70 nm (OD value of 2) is typically used. In this manner, by using a tin oxide (SnO) film containing silicon (Si) as the absorbing film 4 (absorbing film pattern 14a), it becomes possible to make the absorbing film 4 (absorbing film pattern 14a) thinner while maintaining the OD value that indicates the basic performance of the reflective photomask blank 10 and the reflective photomask 20.
[0033] Next, in order to evaluate the influence of the projection effect, a simulation was performed to compare how the HV bias value changes when the film thickness is changed for a tantalum (Ta) film and a tin oxide (SnO) film containing silicon (Si). The HV bias value is the line width difference of the transferred pattern depending on the orientation of the mask pattern, that is, the difference between the line width in the horizontal (H) direction and the line width in the vertical (V) direction. The line width in the H direction indicates the line width of the linear pattern perpendicular to the plane formed by the incident light and the reflected light (hereinafter, sometimes referred to as the "incident plane"), and the line width in the V direction indicates the line width of the linear pattern parallel to the incident plane. In other words, the line width in the H direction is the length parallel to the incident plane, and the line width in the V direction is the length perpendicular to the incident plane.
[0034] The projection effect affects the line width in the H direction, resulting in a decrease in contrast at the edge of the transferred pattern and a decrease in the line width in the H direction. A pattern affected by the projection effect will have a line width smaller than the desired line width after transfer. On the other hand, the line width in the V direction is hardly affected by the projection effect. This results in a line width difference (HV bias) between the line width of the transferred pattern in the direction perpendicular to the incident plane and the line width of the transferred pattern in the direction parallel to the incident plane. Here, the HV bias values of the existing tantalum (Ta) film (film thickness 60 nm) and tin oxide (SnO) film containing silicon (Si) (film thickness 26 nm) were compared, and as shown in Table 2, the HV bias value was very large at 7.3 nm for the tantalum (Ta) film, but was significantly reduced to 4.0 nm for the tin oxide (SnO) film containing silicon (Si), which is an improvement. Thus, it can be seen that in the reflective photomask blank 10 and reflective photomask 20 of this embodiment, the influence of the projection effect (HV bias) can be significantly reduced by using a tin oxide (SnO) film containing silicon (Si) as the material for forming the absorbing film 4 (absorbing film pattern 14a).
[0035] As described above, in order to provide thermal resistance, it is preferable that the material used for the absorbing film 4 (absorbing film pattern 14a) is an oxide rather than an element. In order to provide thermal resistance, it is necessary that the element and oxygen are reliably bonded to each other. In other words, as the tin oxide (SnO) film and the indium oxide (InO) film used for the absorbing film 4 (absorbing film pattern 14a) of this embodiment, it is preferable that the tin oxide (SnO) film has an atomic ratio (O / Sn) of oxygen (O) to tin (Sn) of 1.5 or more and 2.5 or less, and the indium oxide (InO) film has an atomic ratio (O / In) of oxygen (O) to indium (In) of 1.0 or more and 2.0 or less.
[0036] FIG. 6 is a schematic cross-sectional view showing an absorbing film pattern 14a after electron beam correction etching when a reflective photomask 20 is produced by selecting tin oxide (SnO) as the main component (forming material) of the absorbing film 14. In electron beam correction etching, etching gas such as fluorine-based gas (XeF2) is supplied while irradiating the area to be etched with an electron beam, promoting the reactivity of the fluorine etchant and etching tin oxide (SnO). However, tin oxide (SnO) has a high etching resistance to fluorine-based gas and takes an extremely long time to etch, which can cause damage perpendicular to the etching direction, called side etching BS, as shown in Figure 6, 14b. If the side etching BS is large, the line width of the area etched by electron beam correction is significantly shifted, so the high etching resistance to etching gas and the extremely long etching time are one of the reasons for correction failure.
[0037] Therefore, by using tin oxide (SnO), a material that is easily etched by fluorine-based gas, that is, a material whose boiling point of a fluorine-based compound is 250°C or less, as the absorbing film 4 (absorbing film pattern 14a), the repair etching rate is improved and the side etching BS can be suppressed to 2 nm or less, so that the success rate of electron beam repair etching can be improved. Therefore, when the repair side etching BS is 2 nm or less by fluorine-based gas, it can be said that the material has a fast repair etching rate. The same is true when indium oxide (InO) is used as 4 (absorbing film pattern 14a).
[0038] In addition, if the underlying protective film 13 is etched by electron beam correction etching using fluorine gas, electron beam correction etching using chlorine gas (NOCl) is possible. Indium oxide (InO) is not easily etched by chlorine gas, so side etching BS may occur in the same way. In that case, by using indium oxide (InO) containing a material that is easily etched by chlorine gas, that is, a material whose boiling point of a chlorine compound is 250°C or less, as the absorbing film 4 (absorbing film pattern 14a), the correction etching rate is improved and side etching BS can be suppressed, so that the success rate of electron beam correction etching can be improved.
[0039] In order to realize the above etching process, the material to be mixed into the absorbing film 4 (absorbing film pattern 14a) is preferably a material that can be etched by electron beam correction with a fluorine-based gas or a chlorine-based gas, that is, a fluorine-based compound or a chlorine-based compound with a boiling point of 250°C or less. Specifically, as shown in Table 1, silicon, antimony, iridium, osmium, rhenium, tungsten, germanium, arsenic, vanadium, selenium, molybdenum, and tantalum are preferable as mixed materials that are easily etched by fluorine-based gas. Silicon, chromium, germanium, arsenic, vanadium, titanium, tantalum, aluminum, and the like are preferable as mixed materials that are easily etched by chlorine-based gas. In addition, oxides, nitrides, oxynitrides, or boron nitrides of these mixed materials may be used. In addition, a mixed gas of a fluorine-based gas and a chlorine-based gas may be used as an etching gas.
[0040] In this manner, the absorbing film 4 (absorbing film pattern 14a) according to this embodiment contains a material whose correction etching rate during electron beam correction is faster than the correction etching rate during electron beam correction of an absorbing film (absorbing film pattern) composed of at least one of tin oxide (SnO) and indium oxide (InO). Here, the "material whose correction etching rate during electron beam correction is faster" refers to the above-mentioned "material that can be etched by electron beam correction with a fluorine-based gas or a chlorine-based gas."
[0041] In addition, if the mixed material reduces resistance to chemicals such as SPM (sulfuric acid peroxide) and APM (ammonia-hydrogen peroxide mixture) commonly used for mask cleaning, causing problems such as roughening the absorbing film surface and adversely affecting reflectance, a cleaning-resistant layer of about 1 to 5 nm may be provided on the absorbing film 4 (absorbing film pattern 14a).As an alternative method, a cleaning-resistant coating film may be provided to cover the absorbing film 4 (absorbing film pattern 14a) or the capping layers 3 and 13 exposed on the mask surface. Materials for use in cleaning resistant layers or coatings include, for example, materials containing at least one of the following compounds: SiO2, SiON, TaO, TaN, TaBN, CrN, CrON, CrO, TiO2.
[0042] [Example 1] Hereinafter, examples of the reflective photomask blank and photomask according to the present invention will be described with reference to figures and tables. As shown in Fig. 7, a multilayer reflective film 12 was formed by stacking 40 laminated films each consisting of a pair of silicon (Si) and molybdenum (Mo) on a synthetic quartz substrate 11 having low thermal expansion characteristics. The thickness of the multilayer reflective film 12 was 280 nm. Next, a capping layer 13 made of ruthenium (Ru) was formed as an intermediate film on the multilayer reflective film 12 to a thickness of 2.5 nm. As a result, a reflective portion having the multilayer reflective film 12 and the capping layer 13 was formed on the substrate 11. An absorbing film 14 made of tin oxide (SnO) and silicon (Si) was formed on the capping layer 13 to a thickness of 26 nm. The atomic ratio of tin (Sn), oxygen (O), and silicon (Si) was 31.7:68.3:5.0 as measured by XPS (X-ray photoelectron spectroscopy). In addition, when measured by XRD (X-ray diffraction), it was found to be amorphous, although slight crystallinity was observed.
[0043] Next, a back surface conductive film 15 made of chromium nitride (CrN) was formed to a thickness of 100 nm on the side of the substrate 11 on which the multilayer reflective film 12 was not formed, thereby producing a reflective photomask blank 100. A multi-target sputtering device was used to deposit each film on the substrate 11. The thickness of each film was controlled by the sputtering time. For the above-mentioned tin oxide (SnO) film containing silicon (Si), the reflectance R0 of the reflective layer region and the reflectance R of the absorbing film region were measured using a reflectance measuring device using EUV light. From the measurement results, the OD value, which is a mask characteristic, was calculated, and it was found that an EUV reflectance of 0.08% and an OD value of 2.9 could be achieved, as shown in Table 2.
[0044] Next, a method for producing the reflective photomask 200 will be described with reference to FIGS. As shown in FIG. 8, a positive chemically amplified resist (SEBP9012: manufactured by Shin-Etsu Chemical Co., Ltd.) was spin-coated to a thickness of 120 nm on the absorbing film 14 provided on the reflective photomask blank 100, and baked at 110° C. for 10 minutes to form a resist film 16. Next, a predetermined pattern was drawn on the resist film 16 formed of a positive chemically amplified resist using an electron beam lithography machine (JBX3030: manufactured by JEOL Ltd.). After that, a baking process was performed at 110° C. for 10 minutes, and then spray development (SFG3000: manufactured by Sigma Meltec Co., Ltd.) was performed. As a result, a resist pattern 16a was formed as shown in FIG.
[0045] Next, as shown in Fig. 9, the absorbing film 14 was patterned by dry etching using a mixture of chlorine-based gas and fluorine-based gas as the main gas, with the resist pattern 16a as an etching mask, to form an absorbing film pattern 14a. Here, the resist selectivity was calculated, and the selectivity was marked as "◯" when it was improved compared to the existing 100% tin oxide (SnO) film or 100% indium oxide (InO) film, and marked as "X" when it was worse. The comparison target was a film with the same main component as the film. As shown in Table 2, the resist selectivity of this blank was found to be improved compared to a 100% tin oxide (SnO) film.
[0046] 10, the remaining resist pattern 16a was peeled off to form an absorbing film pattern 14a, thereby producing a reflective photomask 200 of Example 1. In Example 1, the absorbing film pattern 14a formed of the absorbing film 14 functioning as a low reflective layer was a line width 64 nm LS (line and space) pattern. This line width 64 nm LS pattern was designed in the x direction and the y direction, respectively, so that the influence of the projection effect caused by EUV irradiation would be easily visible.
[0047] Using an EUV exposure device (NXE3300B: manufactured by ASML), the absorbing film pattern 14a of the reflective photomask 200 produced in each of the examples and each of the comparative examples described later was transferred and exposed onto a semiconductor wafer coated with an EUV positive chemically amplified resist. At this time, the exposure dose was adjusted so that the LS pattern in the x direction was transferred as designed. The transferred resist pattern was observed and line width was measured using an electron beam dimension measuring device to confirm the resolution and HV bias. More specifically, in Example 1, the LS pattern in the y direction was properly transferred, and the HV bias was evaluated in comparison with the case where an existing tantalum (Ta) mask was used. That is, when the LS pattern in the x direction was adjusted to be transferred as designed, the LS pattern in the y direction was transferred as designed, and the HV bias was smaller than that when an existing tantalum (Ta) mask was used, it was determined as "passed", and when it was not transferred as designed (the LS pattern in the y direction was not resolved), or when the HV bias was larger than that when an existing tantalum (Ta) mask was used, it was determined as "failed". As shown in Table 2, the LS pattern dimension in the y direction was 12.0 nm and the HV bias was 4.0 nm, compared to the design value of 16.0 nm. In other words, the reflective photomask 200 of Example 1 had a pattern transferability that did not cause any problems in use.
[0048] The above-mentioned "existing tantalum (Ta) mask" is listed in Table 2 as a "reference example." FIG. 11 shows an enlarged view of a part of the absorbing film pattern 14a in the reflective photomask 200. Here, a specific method for performing electron beam correction etching on the absorbing film pattern 14a formed by dry etching using the resist pattern 16a will be explained. First, the absorbing film pattern 14a, which is the top layer, was irradiated with an electron beam in a gas atmosphere of a mixture of fluorine-based gas and oxygen using an electron beam correction machine (MeRiT MG45: manufactured by Carl Zeiss) to perform electron beam correction etching. The fluorine gas flow rate at this time was controlled by a cold trap technique, and the temperature was -26°C for fluorine (hereinafter referred to as the controlled temperature) and -43°C for oxygen. The line width of the side etching BS at this time was measured using a SEM (LWM9045: manufactured by ADVANTEST), and it was confirmed that it was less than 1 nm.
[0049] In the "Judgment" column of Table 2, "O" was entered if superiority was found in both OD value and transferability compared to existing tantalum (Ta) masks, "△" was entered if superiority was not found in at least one of OD value and transferability, and "X" was entered if inferiority was found in at least one of OD value and transferability.
[0050] [Table 2]
[0051] [Example 2] The absorbing film 14 was formed of tin oxide (SnO) and silicon (Si) and was deposited to a thickness of 45 nm. The atomic ratio of tin (Sn), oxygen (O), and silicon (Si) was measured by XPS (X-ray photoelectron spectroscopy) to be 16.7:33.3:50.0. The other film formation methods and mask fabrication methods were the same as in Example 1. The etching selectivity (resist selectivity) for the resist film 16 was calculated and found to be better than a film made of 100% tin oxide (SnO).
[0052] In addition, measurements were performed using an EUV light reflectance measuring device, and the OD value, which is a mask characteristic, was calculated. As a result, it was found that the EUV reflectance was 1.8% and the OD value was 1.6, as shown in Table 2. In the transferability evaluation by EUV exposure, the LS pattern dimension in the y direction was 10.7 nm and the HV bias was 5.3 nm, compared to the design value of 16.0 nm. In other words, the reflective photomask 200 of Example 2 had a pattern transferability that was problem-free in use. In the electron beam etching repair, the controlled temperature of the fluorine gas flow rate was -20°C, and the oxygen was -43°C. It was confirmed that the side etching BS at that time was less than 1 nm.
[0053] [Comparative Example 1] The absorbing film 14 was formed of tin oxide (SnO) and silicon (Si) and was deposited to a thickness of 45 nm. The atomic ratio of tin (Sn), oxygen (O), and silicon (Si) was 10.0:20.0:70.0 as measured by XPS (X-ray photoelectron spectroscopy). The other film formation methods and mask fabrication methods were the same as in Example 1. The etching selectivity (resist selectivity) for the resist film 16 was calculated and found to be better than a film made of 100% tin oxide (SnO).
[0054] In addition, measurements were taken using an EUV light reflectance measuring device, and the OD value, which is a mask characteristic, was calculated. As a result, it was found that the mask could be manufactured with an EUV reflectance of 5.1% and an OD value of 1.1, as shown in Table 2. In other words, the EUV light reflectance is higher than that of existing tantalum (Ta) masks. In the transferability evaluation using EUV exposure, the LS pattern dimension in the y direction was 12.9 nm and the HV bias was 3.1 nm, compared to the design value of 16.0 nm. In the electron beam etching repair, the controlled temperature of the fluorine gas flow rate was -20°C, and the oxygen was -43°C. It was confirmed that the side etching BS at that time was less than 1 nm.
[0055] [Example 3] The absorbing film 14 was formed of indium oxide (InO) and molybdenum (Mo) and was deposited to a thickness of 27 nm. The atomic ratio of indium (In), oxygen (O), and molybdenum (Mo) was 38.0:57.0:5.0 as measured by XPS (X-ray photoelectron spectroscopy). The other film forming methods and mask fabrication methods were the same as in Example 1. The etching selectivity (resist selectivity) for the resist film 16 was calculated and found to be better than a film made of 100% indium oxide (InO).
[0056] In addition, measurements were performed using an EUV light reflectance measuring device, and the OD value, which is a mask characteristic, was calculated. As a result, it was found that the EUV reflectance was 1.0% and the OD value was 1.8, as shown in Table 2. In the transferability evaluation by EUV exposure, the LS pattern dimension in the y direction was 11.5 nm and the HV bias was 4.5 nm, compared to the design value of 16.0 nm. In other words, the reflective photomask 200 of Example 3 had a pattern transferability that was problem-free in use. In the electron beam etching repair, the controlled temperature of the fluorine gas flow rate was -20°C, and the oxygen was -43°C. It was confirmed that the side etching BS at that time was less than 1 nm.
[0057] [Example 4] The absorbing film 14 was formed of indium oxide (InO) and molybdenum (Mo) and was deposited to a thickness of 34 nm. The atomic ratio of indium (In), oxygen (O), and molybdenum (Mo) was 24.0:36.0:40.0 as measured by XPS (X-ray photoelectron spectroscopy). The other film forming methods and mask fabrication methods were the same as in Example 1. The etching selectivity (resist selectivity) for the resist film 16 was calculated and found to be better than a film made of 100% indium oxide (InO).
[0058] In addition, measurements were performed using an EUV light reflectance measuring device, and the OD value, which is a mask characteristic, was calculated. As a result, it was found that the EUV reflectance was 2.3% and the OD value was 1.4, as shown in Table 2. In the transferability evaluation by EUV exposure, the LS pattern dimension in the y direction was 11.0 nm and the HV bias was 5.0 nm, compared to the design value of 16.0 nm. In other words, the reflective photomask 200 of Example 4 had a pattern transferability that was problem-free in use. In the electron beam etching repair, the controlled temperature of the fluorine gas flow rate was -20°C, and the oxygen was -43°C. It was confirmed that the side etching BS at that time was less than 1 nm.
[0059] [Comparative Example 2] The absorbing film 14 was formed of indium oxide (InO) and molybdenum (Mo) and was deposited to a thickness of 42 nm. The atomic ratio of indium (In), oxygen (O), and molybdenum (Mo) was 24.0:36.0:40.0 as measured by XPS (X-ray photoelectron spectroscopy). The other film forming methods and mask fabrication methods were the same as in Example 1. The etching selectivity (resist selectivity) for the resist film 16 was calculated and found to be better than a film made of 100% indium oxide (InO).
[0060] In addition, measurements were performed using an EUV light reflectance measuring device, and the OD value, which is a mask characteristic, was calculated. As a result, it was found that the EUV reflectance was 1.0% and the OD value was 1.8, as shown in Table 2. In the transferability evaluation by EUV exposure, the LS pattern dimension in the y direction was 7.0 nm and the HV bias was 9.0 nm, compared to the design value of 16.0 nm. In other words, the reflective photomask 200 of Comparative Example 3 had poorer pattern transferability than the existing tantalum (Ta) mask, and no superiority was found. In the electron beam etching repair, the controlled temperature of the fluorine gas flow rate was -20°C, and the oxygen was -43°C. It was confirmed that the side etching BS at that time was less than 1 nm.
[0061] [Comparative Example 3] The absorbing film 14 was formed of indium oxide (InO) and molybdenum (Mo) and was deposited to a thickness of 50 nm. The atomic ratio of indium (In), oxygen (O), and molybdenum (Mo) was 24.0:36.0:40.0 as measured by XPS (X-ray photoelectron spectroscopy). The other film forming methods and mask fabrication methods were the same as in Example 1. The etching selectivity (resist selectivity) for the resist film 16 was calculated and found to be better than a film made of 100% indium oxide (InO).
[0062] In addition, measurements were performed using an EUV light reflectance measuring device, and the OD value, which is a mask characteristic, was calculated. As a result, it was found that the EUV reflectance was 0.7% and the OD value was 2.0, as shown in Table 2. In the transferability evaluation by EUV exposure, the LS pattern dimension in the y direction was not resolved with respect to the design value of 16.0 nm. In other words, the reflective photomask 200 of Comparative Example 4 had poorer pattern transferability than the existing tantalum (Ta) mask, and no advantage was found. In the electron beam etching repair, the controlled temperature of the fluorine gas flow rate was -20°C, and the oxygen was -43°C. It was confirmed that the side etching BS at that time was less than 1 nm.
[0063] [Comparative Example 4] The absorbing film 14 was formed of indium oxide (InO) and molybdenum (Mo) and was deposited to a thickness of 45 nm. The atomic ratio of indium (In), oxygen (O), and molybdenum (Mo) was 16.0:24.0:60.0 as measured by XPS (X-ray photoelectron spectroscopy). The other film forming methods and mask fabrication methods were the same as in Example 1. The etching selectivity (resist selectivity) for the resist film 16 was calculated and found to be better than a film made of 100% indium oxide (InO).
[0064] In addition, measurements were taken using an EUV light reflectance measuring device, and the OD value, which is a mask characteristic, was calculated. As a result, it was found that the mask could be manufactured with an EUV reflectance of 6.6% and an OD value of 1.0, as shown in Table 2. In other words, the EUV light reflectance is higher than that of existing tantalum (Ta) masks. In the transferability evaluation by EUV exposure, the LS pattern dimension in the y direction was 6.4 nm and the HV bias was 9.6 nm, compared to the design value of 16.0 nm. In other words, the reflective photomask 200 of Comparative Example 5 had poorer pattern transferability than the existing tantalum (Ta) mask, and no superiority was found. In the electron beam etching repair, the controlled temperature of the fluorine gas flow rate was -20°C, and the oxygen was -43°C. It was confirmed that the side etching BS at that time was less than 1 nm. [Industrial Applicability]
[0065] The reflective photomask according to the present invention can be suitably used for forming fine patterns by EUV exposure in the manufacturing process of semiconductor integrated circuits and the like. [Explanation of symbols]
[0066] 1...Substrate 2…Multilayer reflective film 3…Capping layer 4...Absorption membrane 10...Reflective photomask blank (reflective mask blank) 11...Substrate 12…Multilayer reflective film 13…Capping layer 14...Absorption membrane 14a…Absorption film pattern 14b...Electron beam correction etching portion in absorber film pattern 15…Back conductive film 16...Resist film 16a...Resist pattern BS...Side etching 20...Reflective photomask (reflective mask) 100...Reflective photomask blank (reflective mask blank) 200...Reflective photomask (reflective mask)
Claims
1. A substrate; a reflective film having a multilayer structure formed on the substrate and reflecting EUV light; a protective film formed on the reflective film to protect the reflective film; and an absorbing film that absorbs EUV light and is formed on the protective film, the absorbing film includes a material that includes tin oxide or indium oxide and is easily etched by a fluorine-based gas or a chlorine-based gas; The absorbing film has a content of the tin oxide or the indium oxide of 50% or more, the material that is easily etched by a fluorine-based gas is at least one selected from the group consisting of antimony, osmium, rhenium, tungsten, germanium, vanadium, selenium, and molybdenum, as well as oxides, nitrides, oxynitrides, and boron nitrides thereof; The material that is easily etched by a chlorine-based gas is at least one selected from the group consisting of germanium, vanadium, titanium, and aluminum, as well as oxides, nitrides, oxynitrides, and boron nitrides thereof.
2. The thickness of the absorbing film is 45 nm or less; 2. The reflective mask blank according to claim 1, wherein an OD (Optical Density) value is 1.0 or more.
3. The atomic ratio (O / Sn) of oxygen (O) to tin (Sn) in the absorbing film is in the range of 1.5 to 2.5, 3. The reflective mask blank according to claim 1, wherein an atomic ratio (O / In) of oxygen (O) to indium (In) in the absorbing film is within a range of 1.0 to 2.
0.
4. 4. The reflective mask blank according to claim 1, wherein the absorbing film contains a material having a faster etching rate during electron beam correction compared to an etching rate during electron beam correction of an absorbing film composed only of at least one of tin oxide and indium oxide.
5. The method further includes forming a coating film on the absorbent film and covering the absorbent film, The coating film covering the absorbing film is made of SiO 2 , SiON, TaO, TaN, TaBN, CrN, CrON, CrO, TiO 2 The reflective mask blank according to any one of claims 1 to 4, characterized in that it is formed of
6. The coating film is formed between the protective film and the absorbing film, and covers the protective film. The coating film covering the protective film is made of SiO 2 , SiON, TaO, TaN, TaBN, CrN, CrON, CrO, TiO 2 The reflective mask blank according to any one of claims 1 to 5, characterized in that it is formed of
7. A substrate; a reflective film having a multilayer structure formed on the substrate and reflecting EUV light; a protective film formed on the reflective film to protect the reflective film; and an absorbing film formed on the protective film for absorbing EUV light; the absorbing film includes a material that includes tin oxide or indium oxide and is easily etched by a fluorine-based gas or a chlorine-based gas; The absorbing film has a content of the tin oxide or the indium oxide of 50% or more, the material that is easily etched by a fluorine-based gas is at least one selected from the group consisting of antimony, osmium, rhenium, tungsten, germanium, vanadium, selenium, and molybdenum, as well as oxides, nitrides, oxynitrides, and boron nitrides thereof; A reflective mask characterized in that the material that is easily etched by the chlorine-based gas is at least one selected from the group consisting of germanium, vanadium, titanium, and aluminum, as well as their oxides, nitrides, oxynitrides, and boron nitrides.
8. The thickness of the absorbing film is 45 nm or less; 8. The reflective mask according to claim 7, wherein an OD (Optical Density) value is 1.0 or more.
9. The atomic ratio (O / Sn) of oxygen (O) to tin (Sn) in the absorbing film is in the range of 1.5 to 2.5, 9. The reflective mask according to claim 7, wherein an atomic ratio (O / In) of oxygen (O) to indium (In) in the absorbing film is within a range of 1.0 to 2.
0.
10. 10. The reflective mask according to claim 7, wherein the absorbing film contains a material having a correction etching rate during electron beam correction faster than a correction etching rate during electron beam correction of an absorbing film composed only of at least one of tin oxide and indium oxide.
11. The method further includes forming a coating film on the absorbent film and covering the absorbent film, The coating film covering the absorbing film is made of SiO 2 , SiON, TaO, TaN, TaBN, CrN, CrON, CrO, TiO 2 11. The reflective mask according to claim 7, wherein the reflective mask is formed of
12. The coating film is formed between the protective film and the absorbing film, and covers the protective film. The coating film covering the protective film is made of SiO 2 , SiON, TaO, TaN, TaBN, CrN, CrON, CrO, TiO 2 12. The reflective mask according to claim 7, wherein the reflective mask is formed of
Citation Information
Patent Citations
Reflective mask blank, reflective mask, method for manufacturing the same and method for manufacturing semiconductor
JP2004006798A
Reflective mask blank, reflective photomask and manufacturing method thereof
JP2007207829A
Method of manufacturing reflective mask blank for EUV lithography
JP2015073013A
Reflection type mask blank, reflection type mask, and method for manufacturing reflection type mask blank
JP2019056898A
Reflective photomask blank and reflective photomask
JP2019139085A